The labyrinths of literacy : reflections on literacy past and present - Graff, Harvey J. (Composition, Literacy, and Culture Ser., 1995)
"This book is a compelling collection of essays by one of the pioneers of revisionist approaches to the history of literacy in North America and Europe. It offers original and controversial views on the relation of literacy to society, leading the way for scholars and citizens who are willing to question the importance and function of literacy in the development of society today."--BOOK JACKET.